Evaluating post-fire woody mulch effects on soil and stream nitrogen - Richardson, Mikaela, author; Kampf, Stephanie, advisor; Rhoades, Chuck, advisor; Ross, Matt, committee member; Wilkins, Mike, committee member (Colorado State University. Libraries, 2024)
Severe wildfires often increase nitrogen (N) loss from burned watersheds, impacting downstream water quality, water treatability, and aquatic habitat. Woody mulch is commonly applied to mitigate soil erosion and enhance revegetation post-fire, but it also provides a source of labile carbon (C) that may stimulate microbial immobilization and limit N release from soils. The objective of our study was to evaluate whether mulch application influenced turnover and loss of soil C and N in laboratory leaching trials and hillslope field settings, and then compared post-fire C and N in streams draining mulched and unmulched catchments. In the laboratory, we quantified C and N inputs and leaching outputs from mulched and unmulched soil columns. Within the Cameron Peak fire burn scar in northern Colorado, we compared soil N availability and potential leaching losses between mulched and unmulched hillslope plots. We also measured C, N, and other chemical constituents in streams draining three mulched and three unmulched catchments. In the laboratory leaching studies, mulch added high concentrations of dissolved organic carbon (> 500 mg L-1) and decreased nitrate leaching from soil columns by 27% during repeated simulated rainfall events. In hillslope plots, mulching also reduced soil nitrate, with greater impacts following spring snowmelt when N losses from soils to streams was highest. However, the effect of mulching was not measurable at the catchment scale due to low application rates and mulch extent, paired with high topographic and geomorphic variability amongst the catchments. Our findings show that C inputs from woody mulch can influence soil N retention in burned watersheds when applied at a minimum rate of 5 Mg ha-1; however practical constraints on aerial application may make it challenging to apply enough mulch for any downstream response to be detectable. Coupled with physical erosion protection, the biogeochemical impacts of mulching may facilitate soil and vegetation recovery following severe wildfire and reduce post-fire N losses to streams if sufficiently applied. Therefore, further post-fire rehabilitation efforts should optimize mulch operations by prioritizing sensitive watersheds and treating them with adequate mulch.